2013
DOI: 10.1021/jo400268u
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Aza-Michael Reaction on Acrylate Derivatives

Abstract: A methodology has been developed for an efficient and selective lipase-catalyzed aza-Michael reaction of various amines (primary and secondary) with a series of acrylates and alkylacrylates. Reaction parameters were tuned, and under the optimal conditions it was found that Pseudomonas stutzeri lipase and Chromobacterium viscosum lipase showed the highest selectivity for the aza-Michael addition to substituted alkyl acrylates. For the first time also, some CLEAs were examined that showed a comparable or higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…For example, the wild‐type and Ser105Ala mutant of CAL‐B can catalyze the Michael‐type addition of thiol and amine nucleophiles to a range of α,β‐unsaturated carbonyl compounds . Franssen's group reported a solvent‐dependent chemoselective Michael addition of amines to acrylate or alkyl acrylate esters catalyzed by lipase . Another solvent engineering method based on the thermodynamic behavior of Michael adducts in various polar media was also investigated by Castillo et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the wild‐type and Ser105Ala mutant of CAL‐B can catalyze the Michael‐type addition of thiol and amine nucleophiles to a range of α,β‐unsaturated carbonyl compounds . Franssen's group reported a solvent‐dependent chemoselective Michael addition of amines to acrylate or alkyl acrylate esters catalyzed by lipase . Another solvent engineering method based on the thermodynamic behavior of Michael adducts in various polar media was also investigated by Castillo et al .…”
Section: Introductionmentioning
confidence: 99%
“…20 Franssen's group reported a solvent-dependent chemoselective Michael addition of amines to acrylate or alkyl acrylate esters catalyzed by lipase. 21 Another solvent engineering method based on the thermodynamic behavior of Michael adducts in various polar media was also investigated by Castillo et al to control chemoselectivity, and the aza-Michael adducts were exclusively obtained in moderate yields. 22 However, these reported enzymatic systems also have some drawbacks, such as low chemoselectivity, lengthy reaction time, and use of hazardous organic media.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when diamines were used as nucleophiles (1,3‐propanediamine and 1,12‐dodecyldiamine), the lipase catalyzed exclusively the addition through one of the amino groups. Chromobacterium viscosum lipase and Pseudomonas stutzeri lipase have served among other lipases to perform the reaction between primary or secondary amines or linear amino alcohols and a series of acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl crotonate and methyl methacrylate (Scheme ) . A clear preference was observed for the chemoselective formation of the 1,4‐addition aza‐Michael products, although in some cases significant amounts of the aminolysis reaction and the 1,4‐addition followed by subsequent aminolysis were observed (up to 29%).…”
Section: Carbon–heteroatom Bond‐formation Reactionsmentioning
confidence: 99%
“…As a "hidden skill" of enzyme, it can provide novel synthesis pathway that are currently not available [5,6] and can widen the application of enzyme. In this area, lipase is the most used 25 enzyme due to its broad specificity and excellent stability in various media. Many elegant works of lipase catalytic promiscuity in the carbon-carbon bond-forming reactions (Aldol condensation, Morita-Baylis-Hillman reaction, Michael addition, Markovnikov addition, and Knoevenagel reaction, et al) have 30 been reported in the past few years [7][8][9][10][11][12][13][14].…”
Section: Moreover This Protocol Extends the Phenomenon Of Enzyme Promentioning
confidence: 99%
“…Since the yield was found to be the highest at 55 o C, the optimum temperature for this reaction was 55 o C. 20 30 Reaction condition: 2-hydroxy-1,4-naphthoquinone (1 mmol), malononitrile (1 mmol) and benzaldehyde (1 mmol), ethanol (2mL), CSL (20 mg, protein content), 12h at different temperature. 25 To explore the scope and feasibility of this multi-component reaction, a series of benzo[g]chromene derivatives were synthesized under the optimum reaction conditions. The results in Table 2 demonstrated that the protocol could be applied to aromatic aldehydes either with electronwithdrawing groups (Entry 2-6) or electron-donating groups (Entry 7-9) 30 with satisfied yields (from 81% to 93%).…”
Section: Moreover This Protocol Extends the Phenomenon Of Enzyme Promentioning
confidence: 99%